2012
DOI: 10.1002/adfm.201102566
|View full text |Cite
|
Sign up to set email alerts
|

Robust Hollow Spheres Consisting of Alternating Titania Nanosheets and Graphene Nanosheets with High Photocatalytic Activity for CO2 Conversion into Renewable Fuels

Abstract: Robust hollow spheres consisting of molecular‐scale alternating titania (Ti0.91O2) nanosheets and graphene (G) nanosheets are successfully fabricated by a layer‐by‐layer assembly technique with polymer beads as sacrificial templates using a microwave irradiation technique to simultaneously remove the template and reduce graphene oxide into graphene. The molecular scale, 2D contact of Ti0.91O2 nanosheets and G nanosheets in the hollow spheres is distinctly different from the prevenient G‐based TiO2 nanocomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
300
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(309 citation statements)
references
References 58 publications
2
300
0
3
Order By: Relevance
“…Second, electron transfer could be promoted in the direction from TiO 2 CB to external trappers or carriers. The electron trappers can be noble metals (e.g., Pt, Pd, Au, Ag) (Sasirekha et al, 2006;Iizuka et al, 2011;Yui et al, 2011;An et al, 2012;Uner and Oymak, 2012;Wang et al, 2012b) or metal oxides (e.g., CuO, FeO x , CeO 2 ) (Tseng et al, 2004;Qin et al, 2011;Srinivas et al, 2011;Wang et al, 2011b;Truong et al, 2012;Zhao et al, 2012b), and the electron carriers are often carbon materials (e.g., graphene) (Liang et al, 2011(Liang et al, , 2012Tu et al, 2012). Third, the incorporation of TiO 2 with another semiconductor, i.e., photo-sensitizer (e.g., AgBr, CdSe, PbS) Asi et al, 2011;Wang et al, 2011a;An et al, 2012) or n-type semiconductor (e.g., ZnO) (Xi et al, 2011), promotes electron transfer between the CB of the second semiconductor and the CB of TiO 2 .…”
Section: Effect Of Materials Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, electron transfer could be promoted in the direction from TiO 2 CB to external trappers or carriers. The electron trappers can be noble metals (e.g., Pt, Pd, Au, Ag) (Sasirekha et al, 2006;Iizuka et al, 2011;Yui et al, 2011;An et al, 2012;Uner and Oymak, 2012;Wang et al, 2012b) or metal oxides (e.g., CuO, FeO x , CeO 2 ) (Tseng et al, 2004;Qin et al, 2011;Srinivas et al, 2011;Wang et al, 2011b;Truong et al, 2012;Zhao et al, 2012b), and the electron carriers are often carbon materials (e.g., graphene) (Liang et al, 2011(Liang et al, , 2012Tu et al, 2012). Third, the incorporation of TiO 2 with another semiconductor, i.e., photo-sensitizer (e.g., AgBr, CdSe, PbS) Asi et al, 2011;Wang et al, 2011a;An et al, 2012) or n-type semiconductor (e.g., ZnO) (Xi et al, 2011), promotes electron transfer between the CB of the second semiconductor and the CB of TiO 2 .…”
Section: Effect Of Materials Modificationmentioning
confidence: 99%
“…The visible light response of TiO 2 /graphene is attributed to the chemical bonding between TiO 2 and the specific sites of carbon that leads to the narrowing of TiO 2 band gap (Zhang et al, 2010). To date, only a few studies have been conducted on TiO 2 /graphene for CO 2 photoreduction (Liang et al, 2011;Liang et al, 2012;Tu et al, 2012). The defects in graphene and the contact between graphene and TiO 2 will significantly affect the charge transfer and determine the activity and selectivity of CO 2 conversion.…”
Section: Electron Transfer From Tio 2 Cb To Trapping Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In both of these approaches, the void size and the shape of the hollow structure are determined by the nature of the template while the morphology and composition of the shell (material, thickness and porosity) is mainly defined in the coating and removal processes. As a result, a wide variety of hollow NCs with different sizes, shapes, composition, and structures have been produced, using hard templates, such as polymers (polystyrene [54,55], formaldehyde resin [56,57], and poly(methyl)methacrylate [58], silica [59,60] and carbon particles [61]), or soft ones, such as emulsion block copolymer micelles [62], and even gas bubbles [63]. For a comprehensive and up-to-date review on templating approaches see Ref.…”
Section: Synthesis Of Hollow Nanostructuresmentioning
confidence: 99%
“…In the process of constant exploring emission reduction technology, it has been found that photogenerated electronics can change CO 2 to organic compounds with high application value such as methane and methanol. Tu et al [94] prepared hollow spheres consisting of alternating Ti 0.91 O 2 nanosheets and graphene nanosheets with polymer beads as sacrificial templates and via a microwave irradiation technique. The ultrathin Ti 0.91 O 2 nanosheets allow charge carriers to move rapidly onto the surface to take part in the photoreduction reaction and the alternating compact stacking structure allow the photogenerated electron to transfer fast from Ti 0.91 O 2 nanosheets to graphene nanosheets to extend lifetime of the charge carriers.…”
Section: Co 2 Reductionmentioning
confidence: 99%